Bahasa Inggris sebagai Sarana Pemberdayaan Warga Kampung Semar dalam Pariwisata Go Green - Ismiatun, Febti; Sholihah, Fitri Awaliyatush; Ni’mah, Dzurriyyatun (Jurnal SOLMA, 2025)
Background: Limited English proficiency has become a major barrier for the residents of Kampung Semar, Malang, in communicating with foreign tourists, especially amidst ongoing efforts to promote sustainable, community-based go green tourism. This program aims to improve the residents’ basic English communication skills so that they can interact with foreign tourists and support sustainable tourism promotion. Method: To address this challenge, a basic English communication training program was conducted through six face-to-face sessions. The methods used included interactive presentations, group discussions, role-playing, and contextual exercises tailored to the residents’ daily needs and situations. The program’s effectiveness was evaluated through surveys involving 15 participants and semi-structured interviews with three randomly selected individuals. Results: The evaluation results showed a significant improvement in the residents’ basic English communication skills, which supported their ability to introduce the village’s potential and welcome foreign visitors. Residents also demonstrated increased enthusiasm and active participation in promoting local tourism activities. Conclusion: This program proved effective in enhancing the basic English communication skills of residents and shows strong potential for replication in other communities facing similar challenges in developing sustainable tourism.